Activision Blizzard, Inc : equity valuation - Ribeiro, Bernardo Maria Teixeira Esteves Campelo (2018)
This dissertation presents the valuation of Activision Blizzard, Inc, which was based on an in-depth analysis of the company and the video game industry. Activision was fairly valued at $71.16 per share, which represents an upside of 12% compared with the trading price of $63.32 as of December 31st, 2017. Thereby, it is recommended a BUY rating to investors. The valuation was based on three valuation methods: DCF WACC, EVA and Multiples. As a result, the DCF WACC approach reached a $77.24 share price, meaning an upside of 22%. The EVA model resulted in a $64.91 share price of with an upside of 3%. Lastly, the Relative valuation based on 2017 23.2x EV&EBITDA and 2017 6.0 P/BV resulted in a share price of $71.51, representing an upside of 13%. The Peer Group used to the Multiples valuation was Electronic Arts, Take-Two and Ubisoft. To conclude, the results achieved were compared with Credit Suisse Equity Research, which final recommendation is a BUY, solidly supporting the findings developed in this Dissertation.